Benefits of strength training for high-performance athletes in anterior cruciate ligament rehabilitation (Research, Society and Development, 2025)
This article aimed to analyze the benefits of strength training in the rehabilitation of high-performance athletes after anterior cruciate ligament (ACL) reconstruction. A literature review identified studies conducted between 2015 and 2025 that addressed resistance exercise protocols and their effects on joint function, muscle strength, and return to sport. The results indicate that quadriceps, hamstring, and gluteal deficits are common after surgery, impacting dynamic stability and athletic performance. Evidence suggests that strength training, especially eccentric, isokinetic, and functional modalities, promotes gains in hypertrophy, muscle torque, limb symmetry, and athlete confidence. Furthermore, protocols that combine closed and open kinetic chain exercises, combined with neuromuscular and plyometric stimuli, have proven more effective in reducing persistent deficits and preventing relapses. The conclusion is that progressive and well-structured strengthening is essential to accelerate functional recovery and ensure greater athletic longevity.